Digital Health Revolution in India: Transforming Health and Medicine - Rishabh Kumar Rana; Neelesh Kapoor; Dewesh Kumar; Madhur Verma; Gunjan Taneja (Indian Journal of Community Medicine)
Digital innovation and its integration in various parts of lifestyle are inevitable as humans have started to evolve over time. Its integration in our health and various systems is irrefutable. In this position paper, we explore the various aspects of this important component of technology, discuss its evolution over time, discuss the various existing modalities, highlight the regulatory frameworks in India, and elaborate on the different ways it can be integrated in our country’s future health plans. We believe digital health is here to stay and play important role in shaping our lives in terms of our accessibility and other interactions related to health.